Experimental investigation and study of HVOF sprayed WC-12Co, WC-10Co-4Cr and Cr3C2-25NiCr coating on its sliding wear behaviour. (January 2021) - Mishra, Tribhuwan Kishore; Kumar, Arbind; Sinha, S.K.
Abstract: An experimental investigation followed by a comparative study of HVOF sprayed WC-12Co, WC- 10Co4Cr and Cr3 C2 -25NiCr coatings were conducted at three different loads of 20, 40 and 60 N. Sliding wear of coated specimens against hardened EN-32 disc was performed as per the G 99–5 standard at room temperature. The feedstock powders and corresponding coatings were characterized for microstructural studies along with porosity, microhardness, and adhesive bond strength. The experimental results suggest that the stability of the transfer layer plays a significant role in stable wear. The WC-12Co coating shows the best sliding wear resistance, maximum microhardness which was found to be 56.6% and 9.6% higher than WC-10Co-4Cr and Cr3 C2 -25NiCr coatings. The maximum adhesive bond strength was found to be 2.03% and 10.5% higher in WC-12Co than WC-10Co-4Cr and Cr3 C2 -25NiCr. Tribo oxide layer counterbalances to stabilize the wear during high heat generation at higher loads. Various aspects and mechanisms of these improvements are discussed in this paper. Highlights: WC-12 Co coating shows better wear resistance than WC–10Co–4Cr and Cr3 C2 -25NiCr coatings. The stability of the transfer layer governs the wear behaviour of coatings. The transfer layer stabilized after critical sliding distance. Tribo oxide layer counterbalances to stabilize the wear at high heat generation. Maximum adhesive strength exhibited by WC-12Co coating is 10.5% higher than Cr3 C2 -25NiCr